Social Media Platforms and Their Impact on Islamic Doctrine - حبيتر, زينب عبدالله (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research aims to identify social networking programs and their impact on the Islamic faith. Social networking programs are a system of electronic networks and programs that are linked and communicated through between all individuals in the world. The study reached results, the most important of which were: that social networking programs have a great impact on the Islamic faith and in influencing its users, whether this impact is positive or negative. Social networking programs have become today among the most attractive programs and attract millions of Internet users, and have recently developed to become the most widespread and used programs among Internet users, especially among teenagers and young people.